PERANCANGAN USER INTERFACE SISTEM INFORMASI E-REPOSITORY KARYA ILMIAH PADA AKADEMI KEPERAWATAN BAITURRAHMAH PADANG BERBASIS WEB - Nelfira, Nelfira; Arman, Arman; Elizamiharti, Elizamiharti; Sari, Amelia Rafika (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to produce a user interface for scientific work repository information systems that are useful for facilitating the Baiturahmah Nursing Academy in searching for scientific work references online. Scientific works are scientific essays that present general facts and are written according to the correct writing methodology and the truth can be proven, the opinions in scientific works are always accompanied by supporting evidence, for that the process of storing scientific works can be arranged in a structured manner. The management of scientific works from the Baiturrahmah Nursing Academy community is currently still manual, the process to access scientific works is done by borrowing directly from the library. The method used in this research is the Waterfall Model System Development Life Cycle (SDLC) and system design tools using the UML model. While the programming language and database design used the PHP programming language and MySQL database. The results of this study are a scientific work repository application that can be accessed online which provides convenience in the process of storing scientific papers, making it easier for the Baiturrahmah Nursing Academy to find references for writing scientific papers.